In vitro characterization of a pAgo nuclease TtdAgo from Thermococcus thioreducens and evaluation of its effect in vivo - Tang, Ying; Wang, Fei; Wang, Yi; Wang, Yuwei; Liu, Yang; Chen, Zhizhao; Li, Wenqiang; Yang, Shihui; Ma, Lixin (Frontiers in Bioengineering and Biotechnology, 2023)
In spite of the development of genome-editing tools using CRISPR-Cas systems, highly efficient and effective genome-editing tools are still needed using novel programmable nucleases such as argonaute (Ago) proteins to accelerate the construction of microbial cell factories. In this study, a prokaryotic Ago (pAgo) from a hyperthermophilic archaeon Thermococcus thioreducens (TtdAgo) was characterized in vitro. Our results showed that TtdAgo has a typical DNA-guided DNA endonuclease activity, and the efficiency and accuracy of cleavage are modulated by temperature, divalent ions, as well as the phosphorylation and length of gDNAs and their complementarity to the DNA targets. TtdAgo can utilize 5’-phosphorylated（5’P）or 5’- hydroxylated (5’OH) DNA guides to cleave single-stranded DNA (ssDNA) from 30 °C to 95 °C in the presence of Mn2+ or Mg2+, and displayed no obvious preference for the 5’ end-nucleotide of the guide. In addition, single-nucleotide mismatches had little effects on cleavage efficiency, except for mismatches at positions 4 or 8 that dramatically reduced target cleavage. Moreover, TtdAgo performed programmable cleavage of double-stranded DNA at 75 °C. We further introduced TtdAgo into an industrial ethanologenic bacterium Zymomonas mobilis to evaluate its effect in vivo. Our preliminary results indicated that TtdAgo had cell toxicity to Z. mobilis resulting in a reduced growth rate and final biomass. In conclusion, we characterized TtdAgo in vitro and investigated its effect in Z. mobilis in this study, which lays a foundation to develop Ago-based genome-editing tools for recalcitrant industrial microorganisms in the future.